2023
DOI: 10.3390/s23135823
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Central and Regional Pulse Wave Velocity in the Assessment of Arterial Stiffness Depending on Gender in the Geriatric Population

Abstract: Artery stiffness is a risk factor for cardiovascular disease (CVD). The measurement of pulse wave velocity (PWV) between the carotid artery and the femoral artery (cfPWV) is considered the gold standard in the assessment of arterial stiffness. A relationship between cfPWV and regional PWV has not been established. The aim of this study was to evaluate the influence of gender on arterial stiffness measured centrally and regionally in the geriatric population. The central PWV was assessed by a SphygmoCor XCEL, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Although the study concluded comparisons between the different categories and the indices, the study’s sample of healthy adults over 65 was underrepresented. Similar to the study by Brillante et al [ 51 ], where it was found that there were no differences between genders in terms of arterial stiffness measurements, the results obtained by Jannasz et al [ 52 ] supported the notion that gender had no bearing on the likelihood of developing atherosclerosis. It should be emphasised, nevertheless, that the results were primarily focused on female participants, which may have influenced the findings.…”
Section: Using Photoplethysmography For Arterial Stiffness Assessmentsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the study concluded comparisons between the different categories and the indices, the study’s sample of healthy adults over 65 was underrepresented. Similar to the study by Brillante et al [ 51 ], where it was found that there were no differences between genders in terms of arterial stiffness measurements, the results obtained by Jannasz et al [ 52 ] supported the notion that gender had no bearing on the likelihood of developing atherosclerosis. It should be emphasised, nevertheless, that the results were primarily focused on female participants, which may have influenced the findings.…”
Section: Using Photoplethysmography For Arterial Stiffness Assessmentsupporting
confidence: 84%
“…There were no discernible differences between men and women in any of the arterial stiffness measures. Jannasz et al [52] 2023 SphygmoCor XCEL (AtCor Medina, Sydney, Australia) Central and regional PWV cfPWV 118…”
Section: Combining Photoplethysmography With Other Modalities and Usi...mentioning
confidence: 99%
“…Previous studies have shown that age is a key factor influencing pulse wave characteristics [50], and many researchers are exploring methods for assessing vascular aging [51,52]. Parameters such as pulse transit time [53] and pulse wave velocity [54] are considered standards for evaluating vascular stiffness. Some researchers have noted a significant correlation between PPG features obtained from the finger and age [55].…”
Section: Participantsmentioning
confidence: 99%